2019
DOI: 10.3390/f10100885
|View full text |Cite
|
Sign up to set email alerts
|

White-Rot Fungi Control on Populus spp. Wood by Pressure Treatments with Silver Nanoparticles, Chitosan Oligomers and Propolis

Abstract: There is growing interest in the development of non-toxic, natural wood preservation agents to replace conventional chemicals. In this paper, the antifungal activities of silver nanoparticles, chitosan oligomers, and propolis ethanolic extract were evaluated against white-rot fungus Trametes versicolor (L.) Lloyd, with a view to protecting Populus spp. wood. In order to create a more realistic in-service type environment, the biocidal products were assessed according to EN:113 European standard, instead of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
(49 reference statements)
2
22
2
Order By: Relevance
“…The results show that even though its effect on wood properties was mediocre, it could be a welcome addition to wood finishes based on natural ingredients [ 149 , 157 , 158 ]. Due to the proven antifungal properties, however, propolis has also been conceived as a potential natural and an environmentally-friendly wood preservative against moulds and wood-decaying fungi [ 150 , 159 , 160 , 161 , 162 ].…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that even though its effect on wood properties was mediocre, it could be a welcome addition to wood finishes based on natural ingredients [ 149 , 157 , 158 ]. Due to the proven antifungal properties, however, propolis has also been conceived as a potential natural and an environmentally-friendly wood preservative against moulds and wood-decaying fungi [ 150 , 159 , 160 , 161 , 162 ].…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
“…Budija et al [ 158 ] demonstrated that an ethanol extract of propolis 29% from Eastern Slovenia effectively protected Norway spruce wood against brown-rot fungi Antrodia vaillantii and G. trabeum , and a white-rot fungus T. versicolor , resulting in wood mass loss of 5.3%, 7.2% and 4.6%, respectively. Also, poplar wood treated with a propolis solution of 40 mg/mL was more resistant to T. versicolor than untreated wood (mass loss of about 11% vs 20%, respectively, after eight-weeks exposure) [ 162 ]. However, in this case, a gradual decrease of antifungal effects of propolis was observed over time during exposure to fungi.…”
Section: Antifungal Substances Of Animal Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass loss of pine wood treated with 7% propolis extract and exposed to T. versicolor and N. lepideus was 4.2% and 2.5%, respectively [13]. In turn, poplar wood protected with propolis extract in concentrations of 5-40 mg/mL after four weeks of exposure to T. versicolor showed the mass loss in the range of 13.7%-9.8%, compared to the 14% mass loss of the unprotected wood [32]. The weight loss of the wood treated with chitosan oligomers and propolis after 30 days of exposure to T. versicolor was 32.8% compared to 42.3% of the weight loss of the untreated wood [33].…”
Section: Decay Testmentioning
confidence: 99%
“…In turn, Scots pine and paulownia wood treated with Turkish propolis extracts exposed to T. versicolor and Neolentinus lepideus showed a lower mass loss than that of untreated wood [13]. Propolis was also used as a constituent of the preparation containing chitosan, propolis extract and silver nanoparticles in preventing the decay of wood caused by T. versicolor [32,33]. The preparation based on propolis extract, caffeine and organosilanes was tested in protection of wood against brown-rot fungus C. puteana [34].…”
Section: Introductionmentioning
confidence: 99%